A rare presentation of acute heart failure secondary to aggressive uterine leiomyosarcoma metastatic to the myocardium initially diagnosed as hypertrophic obstructive cardiomyopathy - Karass, Michael; Mondal, Pratik; Alkayem, Mohammad; Ojo, Amole; Aronow, Wilbert S.; Puccio, Carmelo (Annals of Translational Medicine; Vol 4, No 19 (October 15, 2016): Annals of Translational Medicine, 2016)
Uterine sarcoma is the cause of 3–9% of all uterine malignant neoplasms and has a 2-fold higher incidence in black women as compared to white women. Cellular atypia and abundant mitoses (≥10 per 10 high power fields) as seen in this patient are associated with an increased risk for metastases. Metastases to the heart are infrequently reported with a handful of cases in the literature. We present a case of a 51-year-old woman with aggressively metastatic uterine leiomyosarcoma causing acute heart failure 4 months after initial presentation.